2023
DOI: 10.1186/s13073-023-01233-z
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate GWAS of Alzheimer’s disease CSF biomarker profiles implies GRIN2D in synaptic functioning

Alexander Neumann,
Olena Ohlei,
Fahri Küçükali
et al.

Abstract: Background Genome-wide association studies (GWAS) of Alzheimer’s disease (AD) have identified several risk loci, but many remain unknown. Cerebrospinal fluid (CSF) biomarkers may aid in gene discovery and we previously demonstrated that six CSF biomarkers (β-amyloid, total/phosphorylated tau, NfL, YKL-40, and neurogranin) cluster into five principal components (PC), each representing statistically independent biological processes. Here, we aimed to (1) identify common genetic variants associate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Notably, in contrast to DEGs, the number of DE peaks was substantially different between immature and inhibitory neurons. While in the former we observed a large number of differential peaks (41,341 in AD/NCI, 94 up and 41,247 down; 67,532 total in AD/YA, 67 of them were up and 67,465 down), in GABA neurons the effect was smaller. There were 1659 DE peaks in AD/YC (39 up, 1620 down) and only 87 in AD/HA (8 up, 79 down) (Figure 6I,J).…”
Section: Pro Le Of Inhibitory Neurons In Relation To Age and Diagnosismentioning
confidence: 56%
See 1 more Smart Citation
“…Notably, in contrast to DEGs, the number of DE peaks was substantially different between immature and inhibitory neurons. While in the former we observed a large number of differential peaks (41,341 in AD/NCI, 94 up and 41,247 down; 67,532 total in AD/YA, 67 of them were up and 67,465 down), in GABA neurons the effect was smaller. There were 1659 DE peaks in AD/YC (39 up, 1620 down) and only 87 in AD/HA (8 up, 79 down) (Figure 6I,J).…”
Section: Pro Le Of Inhibitory Neurons In Relation To Age and Diagnosismentioning
confidence: 56%
“…Similarly, several cell types, including neuroblasts and inhibitory neurons secrete NRXN1,3 which binds NLGN2 receptors in immature and CA neurons (Figure 7E,F). These pathways play critical roles in synaptic plasticity and are implicated in cognitive de cits and AD dementia [41][42][43][44] . These analyses further inferred ligand-receptor pathways that may play a role in a decline in cell-cell interaction as a function of pathology in immature neurons, as well as ligands and receptors that may be exclusively expressed in immature neurons (Supplemental Figure 8, Supplemental Tables 16,17).…”
Section: Neurogenic Cell Type Communication With the Cellular Environ...mentioning
confidence: 99%
“…Furthermore, GWAS have gained significant attention as they allow researchers to identify genetic variations associated with increased susceptibility or protection against certain diseases. Recently, GWAS have revealed the unique genetic structure of proteins associated with AD ( Neumann et al, 2023 ; Oatman et al, 2023 ; Ta et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed that DNA variants in CHI3L1 could be associated with increased neuronal injury and inflammation, and CSF levels of CHI3L1 could lead to an increased risk of AD. Also, the CHI3L1 expression in both blood and CSF is positively associated with variants in CHI3L1 [36,87]. The suppression of CHI3L1 DNA variants may contribute to lower levels of blood and CSF CHI3L1, which reduces the risk of AD development.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%